2022
DOI: 10.5603/ep.a2022.0056
|View full text |Cite
|
Sign up to set email alerts
|

Rare clinical problem — isolated ACTH deficiency associated with chronic alcohol abuse

Abstract: IAD seems to be a rare cause of hyponatremia. In one of the larger clinical studies, in a group of 185 patients with severe hyponatremia (< 130 mmol/L) only 28 had secondary adrenal insufficiency, but most of them had also deficiencies of other pituitary hormones [4]. The mechanism of hyponatremia in IAD includes a reduced glomerular filtration rate and ineffective inhibition of vasopressin secretion caused by hypocortisolaemia [2, 5]. Because IAD is not associated with deficiency of aldosterone, the mechanism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“… Chronic alcohol intoxication can cause ultra-microscopic pathological changes in the endocrine cells 16 17 18 . …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… Chronic alcohol intoxication can cause ultra-microscopic pathological changes in the endocrine cells 16 17 18 . …”
Section: Discussionmentioning
confidence: 99%
“…Our center has one patient with type 2 diabetes, three hypertensive patients, one cerebral hemorrhage pa- tient five cerebral infarction patients. Furthermore, studies have reported that a history of chronic alcoholism may be associated with the development of IIAD [16,17]. Chronic alcohol intoxication can cause ultra-microscopic pathological changes in the endocrine cells of the rat adenohypophysis, resulting in pituitary damage [18].…”
Section: Potential Pathogenesis Of Idiopathic Isolated Adrenocorticot...mentioning
confidence: 99%